1997
DOI: 10.1097/00003246-199701000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after cardiac surgery complicated by multiple organ failure

Abstract: Patients treated with prolonged multiple system intensive care after heart surgery have a poor outcome with respect to quality of life measured at least 1 yr after discharge from the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 27 publications
5
34
0
Order By: Relevance
“…The other 7 studies 3,7,9,27,28,33,34 showed similar results, with QOL considerably reduced in the prolonged ICU group, particularly in domains reflecting physical activity. In 8 of 9 studies demonstrating a deterioration in QOL, there was a higher early and late mortality.…”
Section: Studies Showing No Improvement/negative Impact On Qolmentioning
confidence: 67%
See 2 more Smart Citations
“…The other 7 studies 3,7,9,27,28,33,34 showed similar results, with QOL considerably reduced in the prolonged ICU group, particularly in domains reflecting physical activity. In 8 of 9 studies demonstrating a deterioration in QOL, there was a higher early and late mortality.…”
Section: Studies Showing No Improvement/negative Impact On Qolmentioning
confidence: 67%
“…The other 16 studies were retrospective (Table 3). 3,7,9,[25][26][27][28][29][30][31][32][33][34][35][36][37] The retrospective studies included 1,438 patients. Two studies were prospective and included 100 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality of life regarding prolonged intensive care [17,18,19], acute respiratory distress syndrome [10,14], MOD and cardiac surgery [9] and MOD including acute renal dysfunction [20] have been studied. However, no studies are available focusing directly on MOD and QOL in a mixed patient group.…”
Section: Ville Pettilä Anne Kaarlola Annikki Mäkeläinenmentioning
confidence: 99%
“…Only a few studies regarding QOL assessment after intensive care have used generic multidimensional measures [3,4,5,6,7,8,9,10]. Problems and limitations with various models measuring QOL are common [11,12].…”
Section: Introductionmentioning
confidence: 99%